The results of the research on cimicifuga extract impact in systematic and local use on structural and functional skin rates in perimenopause, menopause and postmenopause - Ya A Yutskovskaya; A S Sukhanova (IP Berlin A.V., 2015)
Results of studying of efficiency and safety of the combination of medicine Ci-Clim and cosmetic product Ci-Clim (JSC EVALAR, Russia), containing extract of cimicifuga racemosa, for the purpose of correction of structural and functional changes of skin of women in the perimenopausal, menopausal and postmenopausal period are presented. Materials and methods. Under supervision there were 15 women aged from 41 till 56 years, who had any signs of a climacteric syndrome. Research of the morphologic and functional skin characteristics (including measurement of thickness of derma and epidermis by means of ultrasound, the characteristic of structure, humidity, elasticity and visual appearance of skin), and also an assessment of quality of life by means of SF-36 questionnaire was conducted. Patients were treated with combination of medicine Ci-Clim 1 tablet 2 times per day during meal within 12 months, and cosmetic product Ci-Clim on the face (1 ml 2 times a day) daily within 12 months. Repeated visits were performed monthly, an assessment of the morphological and functional properties of the skin were done at 6 and 12 months.Results. Significant reduction of thickness of epidermis and increase in thickness of derma, and also increase of skin humidity and elasticity were noted at 6 and 12 months. Visual characteristics of skin improved. Quality of life of postmenopausal women improved as well as the skin characteristics. Conclusion. Application of the combination of medicine Ci-Clim and cosmetic product Ci-Clim, containing herbal extracts is highly effective, safe and well tolerated drug that allows to achieve effect in treatment of involutional changes of skin, improving an emotional state and quality of life of women.